(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This research explores the effectiveness of the audio-lingual approach in enhancing Arabic language speech competencies within the context of Uzbekistan’s higher education. Focused on the pedagogical experience of the International Islamic Academy of Uzbekistan, the paper investigates the mechanisms of automating speech reflexes through systematic repetition and phonetic modeling. Furthermore, it evaluates the integration of digital tools and gamification elements, such as didactic games and mobile platforms, in overcoming psychological barriers and linguistic interference. The findings suggest that while the audio-lingual method significantly improves phonetic accuracy, its success depends on a balanced integration with communicative strategies to prevent methodological monotony.